PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI (Pada Karyawan Kantor Pelayanan Perbendaharaan Negara/KPPN Solo Raya) - Parji, Parji; Wahyudi, Amin; Wardiningsih, Suprihatmi Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This research aims to analyses (1) significance effect motivation on organizational commitment; (2) significance effect job satisfaction on organizational commitment; (3) significance effect motivation on employee performance (4) significance effect job satisfaction on employee performance; (5) significance effect organizational commitment on employee performance; (6) effect motivation on employee performance mediated organizational commitment (7) effect job satisfaction on employee performance mediated organizational commitment. This study is sensus research, using location in State Treasury Service Office/KPPN Solo Raya, using sample of 109 employees. Data collecting with questionnaire technique through validity and reliability test. To test hypothesis using path analysis.The result shows that (1) motivation have a significance effect on organizational commitment; (2) job satisfaction have a significance effect on organizational commitment; (3) motivation have a significance effect on employee performance; (4) job satisfaction have a significance effect on employee performance; (5) organizational commitment have a significance effect on employee performance; (6) effect of motivation on employee performance mediated organizational commitment (7) effect of job satisfaction on employee performance mediated organizational commitment.